Improving Maharah Qira'ah in Arabic Through SQ3R Method: Meningkatkan Maharah Qira'ah dalam Bahasa Arab Melalui Metode SQ3R - Amirullah, Dzikrul; Anwar, Najih (Universitas Muhammadiyah Sidoarjo, 2024)
The general background indicates that innovative teaching methods are essential in supporting reading proficiency. Specific background focuses on the challenges faced by students in Class VIII C at SMP Tahfidz Muhammadiyah Al Fattah Malang in comprehending Arabic texts. Knowledge gap relates to the lack of research on the application of the SQ3R (Survey, Question, Read, Recite, Review) method in Arabic language education at the middle school level. Aims of this study are to improve students' Maharah Qira’ah through the implementation of the SQ3R method. Results from this classroom action research, conducted over two cycles, reveal significant improvements in students' reading abilities, with percentage increases in indicators reaching 68.4% and 74.45% in Cycle I, and 88.85% and 90.1% in Cycle II. Novelty of this research lies in the systematic application of the SQ3R method in Arabic language instruction, which has been underexplored. Implications suggest that the SQ3R method is not only effective in enhancing Maharah Qira’ah but can also be applied in various educational contexts to improve overall reading skills among students. Highlights: Significant improvement in reading skills observed in two cycles. Systematic application of SQ3R in Arabic language education. Addressed challenges faced by middle school students in comprehending texts. Keywords: Maharah Qira’ah, SQ3R Method, Arabic Education, Classroom Action Research, Reading Proficiency